THE RESOLUTION OF CONFLICT BETWEEN TEACHER AND STUDENT: TEACHERS’ NARRATIVES - Ciuladiene, Grazina; Kairiene, Brigita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The significant thing for teachers is to settle conflicts with students correctly and effectively without disrupting educational process and damaging the relationship. Dispite teacher-student conflicts are unevitable, and important consequences arise there from, teacher-student conflicts remain poorly studied. The present study aims to examine the strategies teachers use to resolve teacher-student conflicts. To investigate the process of conflict between a teacher and a student, a case study method was used. Respondents – teachers - were asked to recall a conflict occurring between them and a student during the school years, describe how the incident was handled, and the consequences of it. The number of respondents constituted 31 teachers. Their average age was 43, 6 years. By gender there were 2 males and 29 females; work experience was from 2 till 35 years.An analysis of the cases enabled to distinguish two groups of teachers’ reactions to the conflicts. One of them is focus on communication with student on the issue and discovering of the reasons of his / her behaviour. Resolving conflict in a cooperative way involves teacher’s endeavours to perceive accurately student’s positions and motivation, recognise the legitimacy of each other’s interests, and search for a solution accommodating the needs of both sides. The second group of teachers’ reactions to the conflicts manifests itself by the lack of the reflection of the motives and causes of the student’s inappropriate behaviour. Thus, recorded conflicts are considered as non cooperative (destructive) ones.This study give insight into the role of teacher in relation to conflict resolution with student. Findings of the study emphasize the need for teachers to critically determine meaningful conflict resolution strategies.